Biomechanical study of the strength of the reconstructed lateral ligaments of the ankle joint - Krasnoperov, Sergiy; Golovakha, Maksim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Arthroscopic techniques of reconstruction in cases of the anterior talofibular ligament (ATFL) and calcaneofibular ligament (CFL) are widely known. However, biomechanical research of strength of restored ligaments under arthroscopic control using suture or anchor devices was not conducted. Objective: to find out the strength of restoration of lateral ligaments of the ankle joint with help of techniques under arthroscopic control (П-shaped suture, anchor devices). Materials: sixteen cadaver ankle joints were used. It was revealed that damage of the ATFL leads to significant increasing in anterior displacement of talus relative to the tibia and to slight increasing of its varus deviation. In case of damage of the CFL, conversely, varus deviation of talus increases significantly and its anterior dislocation increases insignificantly. The strength of the restored ATFL with using of the П-shaped suture was 85 N, and with help of the anchor device was 88.8 N, corresponding to 59 and 62 % of the strength of the intact ligament. The strength of the restored CFL using П-shaped suture was 83.8 N, and with help of the anchor device was 86.3 N, i.e. 24 and 25 % of the strength of the intact ligament. Strength characteristics revealed correspond to these ones in cases of reconstruction of the ligaments with using of the Brostrom technique. Therefore, we believe that early loading (except inversion) in special orthopedic shoes will not affect the outcomes of treatment.